Why we believe in superfoods: investigating attitudes, personality and message processing - Tanis, Martin; Buijzen, Moniek (Frontiers in Communication, 2025)
IntroductionBelief in the benefits of so-called superfoods is widespread, yet little is known about what drives these beliefs, particularly for lesser-known products like moringa.MethodsTwo studies investigated how individual predispositions and information processing styles shape attitudes toward moringa among consumers unfamiliar with it. Study 1 (N = 322) used a correlational design to examine the role of superfoods attitudes, personality traits, thinking styles, and social norms. Study 2 (N = 268) employed an experimental design to test how message processing (central vs. peripheral) moderates these relationships.ResultsAcross both studies, a general positive attitude toward superfoods predicted higher perceived message credibility and more favorable attitudes toward moringa. These effects were especially pronounced under peripheral processing (Study 2). Intuitive thinking and subjective social norms also contributed to positive responses, while analytical thinking and food-health beliefs had weaker or unexpected effects (Study 1).ConclusionFindings suggest that belief in superfoods is shaped more by intuition, affect, and prior attitudes than by analytical evaluation. Health communication strategies should consider these psychological mechanisms when addressing public perceptions of novel health products.